Perlindungan Hukum Terhadap Aparat Kepolisian Yang Melakukan Pembunuhan Berencana - Azizah Nurina Putri; Frans Simangunsong (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Indonesia is a nation that abides by the Constitution of 1945 and Pancasila. Indonesia has encountered a multitude of illicit issues, both collective and individual, in recent years. One such offense is homicide with premeditation. This is a common occurrence in communities, families, and even police departments. Police officers are commonplace individuals who are susceptible to committing unlawful acts, notwithstanding the responsibilities and functions they perform. A considerable number of National Police personnel have been convicted of premeditated homicide. Consequently, the objective of this study is to ascertain the following: 1) the protocols governing the submission of petitions by suspects accused of premeditated homicide committed by police officers; and 2) the legal defense strategies employed by such suspects. The author addressed the issues addressed in this study from two perspectives: an empirical juridical approach and a normative juridical approach. Secondary data was acquired through literature reviews (Library Research), whereas primary data was obtained through field investigations (Field Research). In public trials, police officers occupy the same position as other civilians, according to research findings. Defense efforts may be initiated during a public trial by having the